PELATIHAN PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS WEB BAGI GURU SMP DAN SMA MUHAMMADIYAH KARTASURA - Supriyono, Heru; Sujalwo, Sujalwo; Sapoetra, Adjie; Rahayu, Endah Tri (WARTA, 2015)
A web-based learning media is a learning media developed and run using website technology so that able to display learning material in the form of text, figure or graph and video which is more attractive compared to printed learning material such as moduls or text books. The observation results showed that learning processes conducting in SMP Muhammadiyah 1 Kartasura and SMA Muhammadiyah 4Kartasura mainly are still using printed material. The objective of the community service is to introduce web ?based learning media of volley ball and to improve skillof the teachers by conducting fundamental web development training. Firstly, a webbased volley ball learning media had been developed by using HTML5. The application has some useful features such as theoretical preview of volley ball and its technique including visualisation using graph, picture and video. Secondly, in the web development training session, a content management system (CMS) Wordpress was used as a paltform so that participants did not need to develop web from scratch. The post-tes quesionnaire results showed that all participants have knowledge and skill to use a web-based volley ball learning media and also they have acquired basic skill in web development.